2019
DOI: 10.18006/2019.7(1).42.50
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Traditional Crops for Food and Feed: A Case of Hulless Barley (Hordeum Vulgare) Landraces in Ethiopia

Abstract: This study explored food-feed traits in genotypes of 25 indigenous Ethiopian landraces, 13 landraces introduced into Ethiopia and 5 local checks of hulless barley (Hordeum vulgare). The genotypes were evaluated for straw fodder quality traits and the traits were related to grain yield and straw yield. The genotypes were grown in Ethiopia during the 2016 cropping season using augmented design consisting of 5 complete blocks. Results of the study showed high genotypic variability in grain yield (5.1 t/ha), straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Our study evaluated both grain and straw quality and added HB1963 and Traveller in addition to IBON 174/03. Large variation in food and malt barley cultivars has been demonstrated in several studies (Pearce et al, 1988;Reed and Yilma, 1986;Wamatu et al, 2019). Our study walks the same trail but also adds the insight that not only grain quality but also straw quality showed an interesting range for selection.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study evaluated both grain and straw quality and added HB1963 and Traveller in addition to IBON 174/03. Large variation in food and malt barley cultivars has been demonstrated in several studies (Pearce et al, 1988;Reed and Yilma, 1986;Wamatu et al, 2019). Our study walks the same trail but also adds the insight that not only grain quality but also straw quality showed an interesting range for selection.…”
Section: Discussionsupporting
confidence: 75%
“…All grain and straw samples were analysed for crude protein (CP), neutral detergent fibre (NDF), metabolizable energy (ME) and in vitro organic matter digestibility (IVOMD) using a combination of wet chemistry analyses and Near Infrared Reflectance Spectroscopy (NIRS); Instrument FOSS 5000 Forage Analyzer with WINISI II software package in the 1108-2492 nm spectra range). A good-offitness barley NIRS equation (Wamatu et al, 2019) was used for the prediction of dry matter (DM), nitrogen, neutral detergent fiber (NDF) and in vitro digestibility (IVOMD). Validation of the NIRS equation was undertaken by analyzing 20% of representative samples using conventional wet chemistry.…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…In Ethiopia feeding of ruminant depend on crop residues and poor quality hay. As a result, the digestibility and intake of these feeds are low which results in poor performance (Mekuriaw and Asmare, 2018;Wamatu et al, 2019). Despite the potential economic benefits, cereal grain and concentrate supplementation to low-quality feeds is unaffordable by smallholder farmers in addition to scarcity and its use as human food.…”
Section: Introductionmentioning
confidence: 99%
“…Varietal differences in the chemical composition and feeding value of crop residues have been reported in wheat, rice, sorghum and maize [11]. The authors of [12] showed the high genotypic variability in grain yield, straw yield and the nutrient composition of straw in naked barley landraces. The authors of [6,[13][14][15] found a varietal variation in the intake and nutrient digestibility of barley straw when it was fed to sheep.…”
Section: Introductionmentioning
confidence: 99%